SALES SYSTEMS ON MADJU CV.MENARA USING VISUAL BASIC 6.0 - Rohmat Rohmat (Jurnal Sistem Informasi, 2006)
Sales System is a system that can support operational CV.Menara Madju in improvingservice to customers. System that contains information about products that complete withits specifications include the price. Scientific writing illustrates how to create a designSales System using Visual Basic 6.0.Scientific Writing Hopefully this can help to develop a more Interactive Sales Systemsand Innovative.